Diseño gráfico aplicado a material lúdico para dar a conocer el sistema de correo del Tahuantinsuyo durante el perìodo Octubre 2016 – Agosto 2017 - Pallo Valverde, Nelly Margoth (2017)
The present research has as a goal to transmit 4th grade of primary education kids information about the delivery system of Tahuantinsuyo. Ana Paez School is an institution, which have not information about the delivery system of Tahuantinsuyo. For this reason, a research was carried out, it allowed to consolidate a playful material taking the most important features of this system of ancestral communication. Firstly, some surveys have been taken to Ivonne Arroyo who is a teacher in the institution ,then a demonstrative class was realized to 4th grade of primary education kids because is important that they know about that for the development of the project. Finally, with the playful material that was applied researchers achieved to spread to children a strong knowledge about the delivery system of Tahuantinsuyo and the experience of Chasqui, Checking that through of a playful teaching aids the gamificación methodology it can to transmit information in an educative way, so the system of ancestral communication will be captured and its meaning will endure in time.